Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1016/0010-0285(85)90014-3
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic reasoning schemas

Abstract: We propose that people typically reason about realistic situations using neither content-free syntactic inference rules nor representations of specific experiences. Rather, people reason using knowledge structures that we term pragmatic reasoning schemas, which are generalized sets of rules defined in relation to classes of goals. Three experiments examined the impact of a "permission schema" on deductive reasoning. Experiment 1 demonstrated that by evoking the permission schema it is possible to facilitate pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
611
1
18

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,236 publications
(660 citation statements)
references
References 24 publications
(39 reference statements)
22
611
1
18
Order By: Relevance
“…1.) This spike in performance when the conditional is a social contract has been found widely in industrialized nations (8)(9)(10)(11)17) and, in the accompanying paper, recently has been observed even among isolated, nonliterate hunter-horticulturalists (18). Cognitive experiments have demonstrated that the activation of this heightened performance is sensitively regulated by the series of variables expected if this were a system whose function were to reason specifically about social exchange, rather than about a broader class of contents (8)(9)(10)(11)(12)(13)18).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…1.) This spike in performance when the conditional is a social contract has been found widely in industrialized nations (8)(9)(10)(11)17) and, in the accompanying paper, recently has been observed even among isolated, nonliterate hunter-horticulturalists (18). Cognitive experiments have demonstrated that the activation of this heightened performance is sensitively regulated by the series of variables expected if this were a system whose function were to reason specifically about social exchange, rather than about a broader class of contents (8)(9)(10)(11)(12)(13)18).…”
mentioning
confidence: 74%
“…All of the social contracts and precautions were permission rules [as defined by pragmatic reasoning theory (17,25)] and therefore logically (and deontically) equivalent. The average length of the social contract problems was 153.7 words, and that of the precaution problems was 154.0 words; thus they were well matched for verbal complexity and memory load.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Participants were informed that they were matched with the same group of participants as in the first phase and that they would be randomly rematched with other participants in each of the periods of the second phase. This was done in 4 Psychologists have studied how different isomorphic representations of the same problem or tasks can induce different solution strategies and behavioural outcomes. This is often referred to as the "representation effect", which is closely related to "framing effects" more well known among economists (Tversky and Kahneman 1981; Chen and Holyoak, 1985; Novick 1990; Zhang and Norman 1999).…”
Section: Designmentioning
confidence: 99%
“…Rapoport et al (2000), Cooper andKagel (2003, 2008) 4 The paper is organized as follows. In Section 2 we describe the experimental design.…”
Section: Introductionmentioning
confidence: 99%